(untitled) (Web of Teachers: Inderscience Research, 2024)
This scientific article examines the application of advanced models for forecasting economic indicators that play a crucial role in shaping the business environment. The study focuses on using sophisticated modeling techniques to predict key economic variables that are important for understanding the trajectory of business development. By applying advanced forecasting models, the study aims to provide insight into the dynamic nature of economic indicators and their impact on the overall business landscape.